Approaches to overcoming regional water poverty - Susanne Neubert (Deutsches Institut für Entwicklungspolitik (DIE), 2002)
If attitudes toward water do not change fundamentally, two thirds of the world's population will be affected by water poverty as early as the year 2025. Today, the by far greatest share of water consumed worldwide is used for agricultural irrigation, and population growth and increasingly water-intensive lifestyles are raising the demand for water. Measures aimed at increasing water supply (supply management) are, however, at the same time running up against growing financial and technical limits.In regional terms, water resources are distributed very unevenly, and the countries of the Middle East and North Africa are those most hard hit by water poverty. Since trade in grain is able to compensate only for a limited share of regional water deficits, it is essential to focus on increasingly the efficiency of the irrigation sector and to fully exploit the potential of rainfed farming if the world's population is to have access to sufficient food resources in the future.Even though concepts and strategies of efficient irrigation have long been available, water continues to be wasted in nearly all of the countries of the world. The reason for the problem is not a lack of suitable methods, it is the fact that these methods are not put to proper use; and the reason for this in turn is that the political stage has not yet been set and the institutional groundwork has yet to be laid. And thus groundwater reserves continue to be overexploited, wastewater is still discharged directly into rivers, and rainwater continues to run off unused, even though for decades a wealth of information has been available on the recharging of groundwater resources, water-recycling, collection of rainwater, and erosion control.In recent years international water conferences have reached important consensuses on necessary reforms, though binding decisions are still made at the national level and local levels (decentrally). The reforms urgently called for include reduction of water price subsidies, differentiated water tariffs that reflect water qualities, and promotion of more flexible forms of cooperation. Creation of appropriate land and water rights that set incentives for a sustainable use of water are also of crucial importance. Reforms of this kind are the sine qua non for the success of many technical measures at the local level.In principle, both the private and the public sector can contribute to raising the effeciency of water use. The extent to which private actors and water-users associations take sufficient account of the ecological and social aspects involved is largely a matter of what concrete forms of cooperation are found between public and private actors and whether appropriate political action frameworks are set and adhered to. Development cooperation (DC) can provide important support here, above all in the field of capacity-building.
Keywords: 330